Virtual Prototyping and Performance Analysis of Two Memory Architectures. (31st March 2010) - Muhammad, Huda S.; Sagahyroon, Assim
Abstract : The gap between CPU and memory speed has always been a critical concern that motivated researchers to study and analyze the performance of memory hierarchical architectures. In the early stages of the design cycle, performance evaluation methodologies can be used to leverage exploration at the architectural level and assist in making early design tradeoffs. In this paper, we use simulation platforms developed using the VisualSim tool to compare the performance of two memory architectures, namely, the Direct Connect architecture of the Opteron, and the Shared Bus of the Xeon multicore processors. Key variations exist between the two memory architectures and both design approaches provide rich platforms that call for the early use of virtual system prototyping and simulation techniques to assess performance at an early stage in the design cycle.